Analysis Of Archiving In The Kaliangkrik District Religious Affairs Office - Uswatun Chasanah; Purwanto; Laili Syarifah; Nailatul Muna (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research aims to analyze the archiving and document management process at the Kaliangkrik Religious Affairs Office (KUA) and identify the challenges in archiving practices. The research method used is a descriptive qualitative approach. Data was collected through interviews with the head of the KUA and staff who handle archives. Research data was also collected by directly observing the archiving process at KUA Kaliangkrik. Apart from that, research data was also collected through documentation studies. The research results show that the KUA Kaliangkrik archiving process is carried out carefully, ensuring conformity between data and recording. However, the main challenges faced are limited human resources, inconsistent external data updates, changes in filing systems, and technological infrastructure constraints. Although information technology and electronic systems benefit document access, saving physical space, and document protection, technological infrastructure that has yet to be optimized is an obstacle. In maintaining the security and confidentiality of documents, KUA Kaliangkrik has implemented measures such as using passwords to access electronic documents and storing physical documents in safe cabinets or safes. However, collaboration between archive officers, IT, and KUA management needs to be improved to maintain the security of stored documents. Training archivists, coordinating with external parties, updating electronic filing systems, and increasing document security are steps that can be taken to improve the effectiveness of archiving. By overcoming these challenges, archiving and document management at KUA Kaliangkrik can be more efficient, provide good service, and maintain the security of stored documents.